SCHOOLS AS INFORMATION CHANNEL TO REDUCE ALCOHOL USAGE HABITS AMONG ADOLESCENTS - Saukuma, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The purchase of alcohol and the use of such substances among adolescence is prohibited in Latvia by the legal system of rights. Despite the legal ban alcohol consumption is widespread among Latvian adolescence and starts at very early age. Recent studies show that most of 15-year-olds have consumed alcohol in Latvia. In order to proactively inform and reduce alcohol consumption among young people, a number of information and education programmes have been implemented, mainly in the school environment. Most of these programmes lack an assessment. Consequently, there is a lack of data on the programme effectivity and the link of programme with young people’s knowledge and confidence in their alcohol consumption-related behaviour. The purpose of the study is to identify information channels where adolescence are most frequently gain information, to assess the level of knowledge of grade 9 pupils and its relevance to potential action in alcohol consumption situations. The empirical data of this study is based on a survey with grade 9 pupils. The results of the study show that the school environment is important information channel, but it is essential to offer a diverse information content, involving a number of experts to provide information. High levels of knowledge have a positive impact on young people’s confidence in alcohol consumption-related situations, but do not have a significant impact on alcohol trying rates.